High‐Performance Vertical Organic Electrochemical Transistors. Issue 5 (20th December 2017) - Donahue, Mary J.; Williamson, Adam; Strakosas, Xenofon; Friedlein, Jacob T.; McLeod, Robert R.; Gleskova, Helena; Malliaras, George G.
Abstract: Organic electrochemical transistors (OECTs) are promising transducers for biointerfacing due to their high transconductance, biocompatibility, and availability in a variety of form factors. Most OECTs reported to date, however, utilize rather large channels, limiting the transistor performance and resulting in a low transistor density. This is typically a consequence of limitations associated with traditional fabrication methods and with 2D substrates. Here, the fabrication and characterization of OECTs with vertically stacked contacts, which overcome these limitations, is reported. The resulting vertical transistors exhibit a reduced footprint, increased intrinsic transconductance of up to 57 mS, and a geometry‐normalized transconductance of 814 S m −1 . The fabrication process is straightforward and compatible with sensitive organic materials, and allows exceptional control over the transistor channel length. This novel 3D fabrication method is particularly suited for applications where high density is needed, such as in implantable devices. Abstract : Vertical organic electrochemical transistors are demonstrated with decreased channel length down to 450 nm, while retaining a simple fabrication process. These devices exhibit an intrinsic transconductance of up to 57 mS and a geometry‐normalized transconductance of 814 S m −1 . The reduced spatial footprint and improved device performance are particularly suited for biointerfacing applications.